SOSIALISASI NILAI-NILAI KEARIFAN LOKAL DALAM TRADISI LISAN MASYARAKAT MELAYU JAMBI DI ERA DIGITAL - Rahima, Ade; Zahar, Erlina (Yayasan Cita Cendikiawan Al Kharizmi, 2024)
This socialization activity aims to provide an understanding to the community and students about the importance of inheriting the values ​​of local wisdom of the Jambi Malay oral tradition in the digital era. The issues that are socialized include: 1) How are the efforts to inherit the values ​​of local wisdom in the oral tradition of the Jambi Malay community in the digital era? 2) How many oral traditions of the Jambi Malay community have been documented and recognized as national cultural heritage? 3) What local wisdom values ​​​​in the Jambi Malay oral tradition need to be inherited. The results of the socialization include: 1) Efforts to inherit oral traditions in the Jambi Malay community in addition to being documented and disseminated via the internet, 2) The community and students have an understanding of the values ​​​​of local wisdom contained in the Jambi Malay oral tradition. 3) Local wisdom values ​​​​related to: responsibility, politeness, respect for time, honesty, respect for guests and others.